ASSESSING THE IMPLEMENTATION OF ONE DATA INDONESIA AND DIGITAL HEALTH AGENDA WITHIN THE DECENTRALIZATION ERA - Mustofa, Mustabsyirotul Ummah; M. Arief Virgy; Ahmad Mikail (Universitas Negeri Semarang, 2025)
This study critically examines the implementation of One Data Indonesia in the health sector, with a particular focus on the SATUSEHAT platform, within Indonesia’s decentralized governance framework. While One Data Indonesia has been promoted as a cornerstone of evidence-based policymaking and digital health transformation, its implementation in underdeveloped and fiscally constrained regions remains uneven. Good data governance is vital for effective healthcare delivery as it enables informed decision-making and enhances accountability. Without proper data governance, timely and accurate information dissemination becomes challenging, hindering the design, monitoring, and evaluation of effective policies. This necessitates addressing various aspects of data governance in health, such as data fragmentation in healthcare facilities to central institutions. This study uses qualitative methods with a case approach, including data collection techniques and secondary documents. This research finds that local governments face numerous challenges in aligning with national policies, including limited regional fiscal capacity, administrative constraints, and human resource shortages. They often rely heavily on central government transfers. Additionally, the capacity of local agencies in data management still needs to be improved. In essence, the narrative underscores that good data governance is a collective endeavor, requiring the active and informed participation of diverse stakeholders. This study contributes to the literature by providing empirically grounded insights into how decentralization conditions digital health data governance in developing countries.